The Development of Campervan Ground at Madasari Beach - Baitulloh, Taqiy Gusdi; Nurhayati, Atikah; Prihadi, Donny Juliandri; Dhahiyat, Ahmad Prawira; Arief, Mohamad Candra W. (Journal of Tourism Sustainability, 2025)
Madasari Beach is one of the beaches located in Pangandaran Regency, West Java. The development of campervans is currently very popular globally and internationally, especially after the pandemic. This means the purpose of the research is to develop a campervan ground site at Madasari Beach. This research uses a qualitative research approach with an exploratory descriptive research type. Data collection techniques that use observation, interviews, documents, and archives. Analyzed with an interactive analysis model where activities in qualitative data analysis are carried out interactively and continuously until completion. This research uses QGIS, AutoCAD, and SketchUp in planning the development of campervan ground tourist attractions, and designs the development of the existing campervan ground tourist attraction area by not changing the state of the field too much. In the design, some things such as existing vegetation around, existing roads in related tourist attractions, and main roads leading to or passing through related tourist attractions are maintained. This research concludes that there are several things to consider, such as community participation, user comfort, and natural preservation that are considered. However, there needs to be further research related to tourist attractions, especially based on the point of view of tourism attraction management.